2012
DOI: 10.4038/tar.v23i1.4632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma viride and Carbofuran (Curator<sup>®</sup>) on Management of Root Knot Nematodes and Growth Parameters of Gotukola (Centella asiatica L.)

Abstract: Gotukola (Centella asiatica L) is a widely grown popular leafy vegetable in Sri Lanka. Root Knot Nematodes (RKN) (Meloidogyne spp.) infestation is one of the key problems which causes heavy losses in commercial Gotukola cultivations in warm climates. A field experiment was carried out in Chilaw (AEZ IL1a) during the wet season (Maha) 2010/2011 to evaluate the effectiveness of the bio-control agent, Trichoderma viride and chemical; Carbofuran (Curator®) on RKN and growth of Gotukola. The treatments imposed were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Among the applied control measures, Trichoderma viride proved to be an effective treatment, consistent with the findings of Shamalie et al (2012), which revealed that the application of Trichoderma viride in the soil led to an increase in stalk length to 14.07 cm, root length to 2.97 cm, and top fresh weight to 0.9 gm compared to the untreated control. Similarly, Subedi (2022) discovered that the application of Trichoderma viride in the soil resulted in a dry root weight of 40.75 gm, surpassing the results of the untreated control.…”
Section: Growth Parameters (Plant Height Shoot Weight Root Length And...supporting
confidence: 83%
See 1 more Smart Citation
“…Among the applied control measures, Trichoderma viride proved to be an effective treatment, consistent with the findings of Shamalie et al (2012), which revealed that the application of Trichoderma viride in the soil led to an increase in stalk length to 14.07 cm, root length to 2.97 cm, and top fresh weight to 0.9 gm compared to the untreated control. Similarly, Subedi (2022) discovered that the application of Trichoderma viride in the soil resulted in a dry root weight of 40.75 gm, surpassing the results of the untreated control.…”
Section: Growth Parameters (Plant Height Shoot Weight Root Length And...supporting
confidence: 83%
“…In addition, Shamalie et al (2012) noted that the application of T. viride in soil led to only 13.32% of root gall formation in Centella asiatica. The formation of galls on the roots and the invasion of root tissue by these nematodes deprive plants of vital nutrients (Terefe, 2015), resulting in stunted growth and heightened vulnerability to mild stressors.…”
Section: Root Gall Index and Number Of Root Galls Per Plantmentioning
confidence: 99%
“…It was found from earlier studies that T. viride was used as a bio-control agent which also promoted the growth of certain plants. Shamalie et al ( 2011 ) reported that T. viride possess growth promoting efficacy when tested on Centella asiatica under field trials and moreover, it had bio-control potency against nematode parasites forming root galls. Similar antagonistic potential of Trichoderma viride against various pathogenic fungi of Vigna radiata was also reported (Mishra et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that it is environmentally safe, commercially viable, and provides a sustainable and cost-effective alternative to chemical nematicides, biological management is regarded as the most pertinent and least harmful technique [12]. It can either be natural or induced.…”
Section: Nemataphogous Fungi As Biocontrol Agentsmentioning
confidence: 99%
“…Uniquely, nematophagous fungi stop the nematode by using specific structures designed to combat nematodes. These carnivorous mushrooms play a significant role in regulating nematode concentrations in soil due to their predatory and parasitic behaviors [12].…”
Section: Nemataphogous Fungi As Biocontrol Agentsmentioning
confidence: 99%